Migration, Distribution, and Safety Evaluation of Specific Phenotypic and Functional Mouse Spleen-Derived Invariant Natural Killer T2 Cells after Adoptive Infusion - Dongzhi Chen; Wenbin Xu; Jingfang Teng; Huifang Liu; Yuanyuan Wang; Yan Wang; Shujie Cheng; Ming Meng (Mediators of Inflammation)
Herein, the migration distribution and safety of specific phenotypic and functionally identified spleen-derived invariant natural killer T2 (iNKT2) cells after adoptive infusion in mice were studied. The proliferation and differentiation of iNKT cells were induced by intraperitoneal injection of α-galactosylceramide (α-GalCer) in vivo. Mouse spleens were isolated in a sterile environment. iNKT cells were isolated by magnetic-activated cell sorting columns (MS columns). Cytometric bead array (CBA) assay was used to detect cytokine secretion in the supernatant stimulated by iNKT cells. The basic life status of the mice was observed, and systematic quantitative scoring was conducted after injecting spleen-derived iNKT cells through the tail vein. An in vivo imaging system was used to trace the migration and distribution of iNKT cells in DBA mice. The percentage of the iNKT2 subgroup was the highest in 3 days after intraperitoneal injection of α-GalCer, and iNKT2 subsets accounted for more than 92% after separation and purification by magnetic-activated cell sorting (MACS). Anti-inflammatory cytokine IL-4 was mainly found in the supernatant of cell cultures. The adoptive infusion of iNKT cells into healthy mice resulted in no significant change in the basic life status of mice compared with the noninjected group. iNKT cells were detected in the lung, spleen, and liver, but no fluorescence was detected in lymph nodes and thymus. After dissecting the mice, it was found that there were no significant abnormalities in the relevant immune organs, brain, heart, kidney, lung, and other organs. Intraperitoneal injection of α-GalCer results in a large number of iNKT2 cells, mainly secreting anti-inflammatory cytokine IL-4, from the spleen of mice. After adoptive infusion, the iNKT2 cells mainly settled in the liver and spleen of mice with a satisfactory safety profile.